2014
DOI: 10.1016/j.neuropharm.2014.01.024
|View full text |Cite
|
Sign up to set email alerts
|

mGluR1 within the nucleus accumbens regulates alcohol intake in mice under limited-access conditions

Abstract: Idiopathic or alcohol-induced increases in the expression and function of the Group1 metabotropic glutamate receptor subtype 1 (mGluR1) within the extended amygdala are theorized to contribute to an individual’s propensity to consume excessive amounts of alcohol. In the past, the detailed study of the functional relevance of mGluR1 for alcoholism-related behaviors in animal models was hampered by the poor solubility and non-specific side effects of available inhibitors; however, the advent of the highly potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 39 publications
6
73
1
Order By: Relevance
“…3 & 4). The negative findings regarding the effects of intra-NAc AAV-Homer2b infusion upon the intake of, and preference for, sweet solutions in rats are consistent with nearly a decade of evidence from studies of mice indicating that Homer2, or its associated mGluRs, do not contribute in any significant manner to regulating the rewarding/reinforcing properties of sweet solutions (e.g., Cozzoli et al, 2009, 2012; Lum, Campbell, Rostock, & Szumlinski, 2014; Szumlinski, Ary, Lominac, et al, 2008; Szumlinski et al, 2005). As such, the present drinking data provide the first cross-species evidence that NAc Homer2 actively regulates alcohol intake, without influencing the neural processes underpinning fluid consumption or the hedonic value of non-drug, highly palatable, positive reinforcers.…”
Section: Discussionsupporting
confidence: 68%
“…3 & 4). The negative findings regarding the effects of intra-NAc AAV-Homer2b infusion upon the intake of, and preference for, sweet solutions in rats are consistent with nearly a decade of evidence from studies of mice indicating that Homer2, or its associated mGluRs, do not contribute in any significant manner to regulating the rewarding/reinforcing properties of sweet solutions (e.g., Cozzoli et al, 2009, 2012; Lum, Campbell, Rostock, & Szumlinski, 2014; Szumlinski, Ary, Lominac, et al, 2008; Szumlinski et al, 2005). As such, the present drinking data provide the first cross-species evidence that NAc Homer2 actively regulates alcohol intake, without influencing the neural processes underpinning fluid consumption or the hedonic value of non-drug, highly palatable, positive reinforcers.…”
Section: Discussionsupporting
confidence: 68%
“…The 200 nl/side of fluid injected in the current study is less than what has been injected into the NACsh in previous studies [64, 65]. A built-in control for determining diffusion is histological misses.…”
Section: Discussionmentioning
confidence: 85%
“…Further, dysphoric states during withdrawal are mediated by changes in Acb neurotransmission, with alcohol-induced reductions in monoaminergic function theorized to contribute to the depressive effects of alcohol withdrawal. [23, 74, 75], Moreover, we know that a chronic history of binge drinking elevates indices of glutamatergic signaling within the Acb [15, 73]. Thus, we hypothesized at the outset of this study that a history of binge drinking would augment Acb cellular activity, particularly within the AchSh, and this increased activity would correlate with behavioral indices of negative affect.…”
Section: Discussionmentioning
confidence: 98%
“…The AcbSh and AcbC are both anatomically and functionally distinct [71], although both Acb subregions have been implicated in governing different aspects of alcohol reward and alcohol reward-related learning [72] and prior immunoblotting studies indicated changes in excitatory neurochemistry within these subregions in alcohol-experienced animals [15, 23, 63, 73, 74]. Further, dysphoric states during withdrawal are mediated by changes in Acb neurotransmission, with alcohol-induced reductions in monoaminergic function theorized to contribute to the depressive effects of alcohol withdrawal.…”
Section: Discussionmentioning
confidence: 99%